Impact of Triclosan on Female Reproduction through Reducing Thyroid Hormones to Suppress Hypothalamic Kisspeptin Neurons in Mice - Cao, Xin-Yuan; Hua, Xu; Xiong, Jian-Wei; Zhu, Wen-Ting; Zhang, Jun; Chen, Ling (Frontiers in Molecular Neuroscience, 2018)
Triclosan (TCS), a broad-spectrum antimicrobial agent, is widely used in clinical settings and various personal care products. The aim of this study was to evaluate the influence of TCS on reproductive endocrine and function. Here, we show that the exposure of adult female mice to 10 or 100 mg/kg/day TCS caused prolongation of diestrus, and decreases in antral follicles and corpora lutea within 2 weeks. TCS mice showed decreases in the levels of serum LH, FSH and progesterone, and GnRH mRNA with the lack of LH surge and elevation of prolactin (PRL). TCS mice had lower kisspeptin immunoreactivity and kiss1 mRNA in anteroventral periventricular nucleus (AVPV) and arcuate nucleus (ARC). Moreover, the estrogen (E2)-enhanced AVPV-kisspeptin expression was reduced in TCS mice. In addition, the serum thyroid hormones (triiodothyonine and thyroxine) in TCS mice were reduced with increases in levels of TSH and TRH. In TCS mice, the treatment with L-thyroxine (L-T4) corrected the increases in PRL, TSH and TRH; the administration of L-T4 or type-2 dopamine receptors agonist quinpirole inhibiting PRL release could rescue the decline of kisspeptin expression in AVPV and ARC; the treatment with L-T4, quinpirole or the GPR45 agonist kisspeptin-10 recovered the levels of serum LH and FSH and progesterone, and GnRH mRNA. Furthermore, TCS mice treated with L-T4 or quinpirole resumed regular estrous cycling, follicular development and ovulation. Together, these results indicate that exposing adult female mice to TCS (≥10 mg/kg) reduces thyroid hormones causing hyperprolactinemia that then suppresses hypothalamic kisspeptin expression, leading to deficits in reproductive endocrine and function.